Questions kids ask about how things work - Comely, Richard; Dickie, Alison (Grolier] [Toronto, 1989)
Questions Kids Ask About How Things Work answers children's curious inquiries about the mechanics and science behind everyday objects and technologies, sparking a deeper understanding of the world around them.